2022
DOI: 10.3390/ijerph191912160
|View full text |Cite
|
Sign up to set email alerts
|

The “Forgotten Grievers”: The Impact of Pupil Suicide on Post-Trauma and Grief Symptoms in School Staff

Abstract: Background: The suicide of a pupil impacts survivors greatly, but most studies on the subject do not consider school staff, and do not differentiate between the various professional domains. Our aim was to investigate the existence of differences in symptoms of complicated grief as well as post-trauma symptoms after a pupil’s suicide, among school staff in four domains: counsellors, psychologists, principals and home-room teachers. Method: Eighty-four staff members from schools that lost pupils to suicide with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Based on our expertise we believe that staff members from the therapeutic professions, namely psychologists and counselors, may be more willing to dwell on difficult emotional issues such as a student's suicide. Furthermore, staff members who were in closer contact with the deceased student, such as the homeroom teachers, were also more adversely affected by the event, and exhibited significantly elevated levels of complicated grief and PTSD symptoms compared to school counselors and psychologists (Tiech Fire et al, 2022). This finding may also explain why homeroom teachers were less willing to participate in the study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on our expertise we believe that staff members from the therapeutic professions, namely psychologists and counselors, may be more willing to dwell on difficult emotional issues such as a student's suicide. Furthermore, staff members who were in closer contact with the deceased student, such as the homeroom teachers, were also more adversely affected by the event, and exhibited significantly elevated levels of complicated grief and PTSD symptoms compared to school counselors and psychologists (Tiech Fire et al, 2022). This finding may also explain why homeroom teachers were less willing to participate in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Levi-Belz (2015) and Levi et al (2011) estimate that every suicide leaves 25 bereaved "suicide survivors." In cases of suicide among children and adolescents, the school staff constitutes a significant group of grievers, albeit "forgotten grievers" (Tiech Fire et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, several participants had guided their social network to receive the necessary support. In another important study, Tiech Fire and colleagues [ 20 ] focused on school staff, with the aim of understanding the impact of student suicides on post-trauma and grief symptoms among teachers, counsellors, and school principals. The authors found that homeroom teachers suffered more from complicated grief and post-traumatic stress disorder (PTSD) compared to psychologists and counsellors and, as such, should receive more preparatory training.…”
Section: Impact Of Suicide and Adverse Grief Reactionsmentioning
confidence: 99%